Glocalization and the Marketing of Christianity in Early Modern Southeast Asia - Andaya, Barbara Watson (Religions, 2017)
The expansion of European commercial interests into Southeast Asia during the early modern period was commonly justified by the biblical injunction to spread Christian teachings, and by the civilizing influences it was said to foster. In focusing on areas where Christianity gained a foothold or, in the Philippines and Timor Leste, became the dominant faith, this article invokes the marketing concept of glocalization, frequently applied to the sociology of religion. It argues that the historical beginnings of the processes associated with the global/local interface of Christianity are situated in the sixteenth century, when Europe, Asia and the Americas were finally linked through maritime connections. Christian missionizing was undertaken with the assumption that the European-based brand of beliefs and practices could be successfully transported to a very different environment. However, the application of these ideas was complicated by the goal of imposing European economic control, by the local resistance thus generated, and by competition with other religions and among Christians themselves. In this often antagonistic environment, the degree to which a global product could be repackaged and glocalized so that it was appealing to consumers in different cultural environments was always constrained, even among the most sympathetic purveyors. As a result, the glocalization of Christianity set up power-laden tensions which both global institutions and dispersed consumers continue to negotiate.